2018
DOI: 10.1080/1354750x.2018.1501761
|View full text |Cite
|
Sign up to set email alerts
|

Influence of IL-6, IL-10, IFN-γ and TNF-α genetic variants on susceptibility to diabetic kidney disease in type 2 diabetes mellitus patients

Abstract: Although inflammatory cytokine genotypes and, more importantly, haplotypes may have the potential to identify those patients at risk of DKD, hence, improving DKD predisposition prediction, further investigations regarding their real clinical significance is warranted in a large cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…For example, cytokine-mediated signaling pathway, apoptosis signaling pathway, reactive oxygen species metabolic process, regulation of in ammatory response, etc. Relevant studies have shown that the occurrence and development of DN is related to cell dysfunction and damage [ 40 , 41 ], chronic in ammatory in ltration [ 42 ], cell apoptosis, and oxidative stress [ 43 ]. This indicates that the main target genes are important for multiple BP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cytokine-mediated signaling pathway, apoptosis signaling pathway, reactive oxygen species metabolic process, regulation of in ammatory response, etc. Relevant studies have shown that the occurrence and development of DN is related to cell dysfunction and damage [ 40 , 41 ], chronic in ammatory in ltration [ 42 ], cell apoptosis, and oxidative stress [ 43 ]. This indicates that the main target genes are important for multiple BP.…”
Section: Discussionmentioning
confidence: 99%
“…1). Ultimately, 14 eligible articles (including 19 independent studies) were selected for the present meta-analysis [12,[21][22][23][24][25][26][27][28][29][30][31][32][33]. Among these, 11 studies exist with outcomes for DN and 8 studies with outcomes for DR to incorporate into this meta-analysis.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…Our results were consistent with most other studies. The study of Rudofsky et al [19] did not find any association between IL-6 -174G/C polymorphism and diabetic neuropathy or diabetic nephropathy in T2DM, which was supported by some other studies [16,17,20]. The study of Paine et al [9] indicated that the promoter polymorphism of IL-6 was not a potent risk factor for the pathogenesis of proliferative diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 81%
“…Studies have confirmed that IL-6 and its expression are associated with insulin resistance and β-cell dysfunction, diabetic retinopathy and obstructive sleep apnea hypopnea syndrome (OSAHS) in T2DM [13][14][15]. However, IL-6 level in T2DM patients with diabetic microvascular complications is considered to be no higher than in patients without complications [16,17]. SNP rs1800795 (-174G/C) of IL-6 gene in T2DM was first reported in 2003 showing that GG phenotype was a genetic determination of inflammation in the development of T2DM [18].…”
Section: Discussionmentioning
confidence: 99%